The COVID -19 Pandemic: Analysis of Large-Scale Social Restrictions (PSBB) Policies for the Community in Various Prevention Efforts - Pujowati, Yenik; Sufaidi, Ahmad (Jurnal Magister Administrasi Publik, 2021)
This study aims to determine the analysis of large-scale social restrictions (PSBB) policies for the community in various efforts to prevent the impact of Coronavirus disease transmission or known COVID-19. The wider the range of transmission of the COVID-19 pandemic, including in Indonesia, the government has taken decisions or steps to immediately break the chain of transmission of the COVID-19 pandemic by making policies, one of which is the large-scale social restriction (PSBB) policy. Government policy N0. 21 of 2020 concerning large-scale social restrictions in the context of accelerating the handling of the COVID-19. The research method is qualitative research with an empirical literature approach. This study uses the library method, namely browsing documents, reports such as journals, post office, books, articles, mass media, or news. The results of this study analyze government policies regarding large-scale social restrictions (PSBB) which have a major impact on people's lives, especially the difficulty of the economy to meet the needs of daily life, especially the lower middle class. PSBB direct impact is devastating for the people who rely on daily income, such as itinerant traders, hawkers, motorcycle taxi operators, drivers and public transportation has. This is one of the impacts of the enactment of the large-scale social restriction (PSBB) policy in Indonesia. From the results of the researchers, it can be concluded that the impact of the virus COVID-19 has resulted in an economic crisis, Learning activities previously carried out in schools today so learn at home online, difficulty to access basic health services, the implementation of the work patterns works from home.